The answers 5 because I looked it up
Answer:
(a+2)(b+2) = 4
Step-by-step explanation:
We are given the following quadratic equation:
![2x^2-3x-6=0](https://tex.z-dn.net/?f=2x%5E2-3x-6%3D0)
Let a a and b be the solution of the given quadratic equation.
Solving the equation:
![2x^2-3x-6=0\\\text{Using the quadratic formula}\\\\x = \dfrac{-b \pm \sqrt{b^2-4ac}}{2a}\\\\\text{Comparing the equation to }ax^2 + bx + c = 0\\\text{We have}\\a = 2\\b = -3\\c = -6\\x = \dfrac{3\pm \sqrt{9-4(2)(-6)}}{4} = \dfrac{3\pm \sqrt{57}}{4}\\\\a = \dfrac{3+\sqrt{57}}{4}, b = \dfrac{3-\sqrt{57}}{4}](https://tex.z-dn.net/?f=2x%5E2-3x-6%3D0%5C%5C%5Ctext%7BUsing%20the%20quadratic%20formula%7D%5C%5C%5C%5Cx%20%3D%20%5Cdfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%5C%5C%5C%5C%5Ctext%7BComparing%20the%20equation%20to%20%7Dax%5E2%20%2B%20bx%20%2B%20c%20%3D%200%5C%5C%5Ctext%7BWe%20have%7D%5C%5Ca%20%3D%202%5C%5Cb%20%3D%20-3%5C%5Cc%20%3D%20-6%5C%5Cx%20%3D%20%5Cdfrac%7B3%5Cpm%20%5Csqrt%7B9-4%282%29%28-6%29%7D%7D%7B4%7D%20%3D%20%5Cdfrac%7B3%5Cpm%20%5Csqrt%7B57%7D%7D%7B4%7D%5C%5C%5C%5Ca%20%3D%20%5Cdfrac%7B3%2B%5Csqrt%7B57%7D%7D%7B4%7D%2C%20b%20%3D%20%5Cdfrac%7B3-%5Csqrt%7B57%7D%7D%7B4%7D)
We have to find the value of (a+2)(b+2).
Putting the values:
![(a+2)(b+2)\\\\=\bigg(\dfrac{3+\sqrt{57}}{4}+2\bigg)\bigg(\dfrac{3-\sqrt{57}}{4}+2\bigg)\\\\=\bigg(\dfrac{11+\sqrt{57}}{4}\bigg)\bigg(\dfrac{11-\sqrt{57}}{4}\bigg)\\\\=\dfrac{121-57}{156} = \dfrac{64}{16} = 4](https://tex.z-dn.net/?f=%28a%2B2%29%28b%2B2%29%5C%5C%5C%5C%3D%5Cbigg%28%5Cdfrac%7B3%2B%5Csqrt%7B57%7D%7D%7B4%7D%2B2%5Cbigg%29%5Cbigg%28%5Cdfrac%7B3-%5Csqrt%7B57%7D%7D%7B4%7D%2B2%5Cbigg%29%5C%5C%5C%5C%3D%5Cbigg%28%5Cdfrac%7B11%2B%5Csqrt%7B57%7D%7D%7B4%7D%5Cbigg%29%5Cbigg%28%5Cdfrac%7B11-%5Csqrt%7B57%7D%7D%7B4%7D%5Cbigg%29%5C%5C%5C%5C%3D%5Cdfrac%7B121-57%7D%7B156%7D%20%3D%20%5Cdfrac%7B64%7D%7B16%7D%20%3D%204)
Answer:
8! or 456 ways
Step-by-step explanation:
8 x 7 x 6 x 5 x 4 x 3 x 2 = 456
Answer:
free points
Step-by-step explanation:
Your question is incomplete.